The conceptual process of skill progression development in artistic gymnastics - Irwin, G.; Hanton, S.; Kerwin, D. G. (Journal of Sports Sciences, 2005)
In this study, we examined the methods used and knowledge required by 16 elite men's gymnastic coaches in the development of skill progressions. Following in-depth interviews, a conceptual model representing the process of skill progression development was generated. We found that: (1) elite gymnastic coaches developed skill progressions through experimental practice, reflection and critical inquiry; (2) the development of skill progressions was underpinned by the coaches acquiring a mindset based on four further sub-components (i.e. skill progression refinement, current coaching knowledge, mental imagery and biomechanical understanding); and (3) coaches identified the importance of replication of the spatial and temporal characteristics of the final skill. The results are consistent with task analysis, reflective practice and the principle of specificity. Practically, these findings suggest the need to develop coaches with a more objective approach to skill progression development and a greater understanding of the controlling mechanisms inherent in such practices.